Measuring stability of virus in aerosols under varying environmental conditions. Issue 12 (22nd October 2021) - Oswin, Henry P.; Haddrell, Allen E.; Otero-Fernandez, Mara; Cogan, Tristan A.; Mann, Jaime F. S.; Morley, Catherine H.; Hill, Darryl J.; Davidson, Andrew D.; Finn, Adam; Thomas, Richard J.; Reid, Jonathan P.
Abstract : Copyright © 2021 American Association for Aerosol Research